PENGARUH CUSTOMER EXPERIENCE, DESAIN ANTARMUKA MOBILE RESPONSIVE, DAN KECEPATAN PEMROSESAN TRANSAKSI TERHADAP ONLINE SATISFACTIONPADA TOKO MAKANAN DI GOFOOD - Erika Decia Putri; Dian Wahyuni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to determine the simultaneous and partial effects of Customer Experience (X1), Mobile Responsive Interface Design (X2), and Transaction Processing Speed (X3) on Online Satisfaction (Y) at food merchants on GoFood. The research method employed is descriptive quantitative, with data analysis conducted using multiple linear regression. The sampling technique utilized is purposive sampling, with the sample size determined by the Krejcie and Morgan formula for an unknown population, resulting in a total of 100 respondents. Validity and reliability tests were performed to ensure the quality of the research instrument. The multiple linear regression analysis yielded the following equation: Y = 6.853 + 0.530 X1 + 0.265 X2 + 0.211 X3 + e. The findings indicate that, simultaneously (F-test), the variables Customer Experience, Interface Design, and Transaction Processing Speed significantly influence Online Satisfaction, with an Fcount of 31.741 > Ftable 2.70 and a significance value of 0.000 < 0.05. Partially (t-test), the results demonstrate a positive and significant impact for each variable: Customer Experience (X1) has a tcount of 4.612 > 1.98472, Interface Design (X2) has a tcount of 3.327 > 1.98472, and Transaction Processing Speed (X3) has a tcount of 2.944 > 1.98472. Based on these results, Customer Experience (X1) is the most dominant variable influencing Online Satisfaction. Furthermore, the coefficient of determination (Adjusted R Square) of 0.482 indicates that this research model accounts for 48.2% of the variance in Online Satisfaction, while the remaining 51.8% is explained by other variables outside the scope of this study.